Tongkonan Papa Batu Tumakke Toraja: an Educational Center for the Culture and Traditions of the Toraja Society - Amirullah Amirullah; Jumadi Jumadi; Ugo Chuks Okolie; Mario Mario (Jurnal Mamangan, 2024)
This research discusses the role and evolution of Tongkonan Papa Batu in Toraja society, especially in Banga Village, from 1671 to 2023. Tongkonan Papa Batu is a typical Toraja traditional house which is unique in its architecture, carvings and cultural role. This research aims to understand cultural diversity, historical values, and changes in the function of Tongkonan Papa Batu from the past to the present. The research method used is a qualitative approach with case studies. Data was obtained through interviews and direct observation. Tongkonan Papa Batu is the main focus, with research covering aspects of architectural uniqueness, Toraja carvings, historical value, and changes in function from the past to modern developments. The results of the research show that  Tongkonan Papa Batu in Banga Village has certain uniqueness, especially in its roof which is made of 1000 pieces of carved stone, creating a historical and cultural attraction. This Tongkonan has been around for approximately 700 years and is the center of traditional, ritual and religious activities. The novelty value of this research is that the change in the function of Tongkonan from a traditional house to a tourist destination also has a positive impact on the economy of the local community.